Public health campaign 2024: pharma assist / Fatin Izyani Azizi and Gurmeet Kaur Surindar Singh - Azizi, Fatin Izyani; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2024)
In a concerted effort to raise awareness and promote safe medication management within the community, a Public Health Campaign 2024 was organised from May 17 to 19. This campaign embarked on a mission to raise awareness in the community regarding safe medication management, with a particular focus on involving students in this crucial initiative. Collaboratively organised by the Society of Pharmacy Students (SOPHYS) 2023/2024, the Sekretariat Mahasiswa Fakulti (SMF) 2023/2024, Majlis Permuafakatan Penduduk Saujana Utama (MPPSU) and the Malaysian Pharmacy Students’ Association (MyPSA), this multifaceted program spanned three impactful days, leaving an impactful mark on all participants.